Ocorrência de esquistossomose na zona urbana, Norte do Estado do Paraná, Brasil - Costa, Aline Balandis (2015)
Schistosomiasisis a major parasitic diseases in the world due to its prevalence and economic consequences on public health in the places where it occurs. It is endemic in many developing countries, especially in Africa, Asia and Latin America. It is estimated that 779 million people are atrisk of infection and 243 million people needed treatment in 2011. In Brazil, schistosomias is has been reported in then or the astern states, southea stand south, affecting approximately six million people. The objective was to verify the status of transmission of schistosomiasis in an urban area of the city of Bandeirantes, Paraná. Trata is a descriptive epidemiologic study, cross-sectional, composed of two stages. In the first stage a retrospective study was done with the use of information obtained from the files of the municipal Bandeirantes. The second stage was a study of population-based sample sands tool tests and a questionnaire. The sample consisted of 304 people. After collection, the fecal samples were keptun der refrigeratio nuntil the exams. The method used was the Kato- Katz. Toanalyze the datawe used the Fischer Exact Test. The history of schistosomiasis cases in Bandeirantes municipality shows that there was a higher prevalence in the years 2005, 2008 and 2009. The new survey showed 9 individuals Schistosoma mansoni contaminated and two cases were classified as moderate/high grade infection. In the an alysis of the exact Fisher test was verified that there is no association between the variables analyzed. The data show that there was a decrease of schistosomiasis cases over the years in the city of Bandeirantes, but the loss of files over the years prevents comparisons with previous data and indicates the neglect in caring for schistosomiasis in this municipality.